The prevalence of subclinical endometritis and intrauterine infections in repeat breeder cows - Pothmann, H. (2015)
The objectives of this study were to assess the prevalence of subclinical endometritis and the presence of common uterine pathogens in repeat breeder cows. A total of 121 cows with three or more consecutive artificial inseminations without conception and no clinical signs of disease were defined as repeat breeder cows and were enrolled in this trial. Intrauterine samples were collected with the cytobrush technique to determine the prevalence of subclinical endometritis and bacteriologic infections. Blood samples were analyzed for concentrations of progesterone and estradiol in plasma to assess ovarian activity. Furthermore, breed, parity, history of calving and postpartum uterine infection, clinical findings of transrectal palpation, and backfat thickness were analyzed as potential factors for the prevalence of subclinical endometritis in repeat breeder cows. The prevalence of subclinical endometritis in repeat breeder cows was 12.7%; but common uterine pathogens, Escherichia coli and Trueperella pyogenes, were found in only one and three cows, respectively. Ovarian activity was determined in 95.0% of all cows. Recorded variables had no effect on the prevalence of subclinical endometritis in repeat breeder cows. In conclusion, subclinical endometritis and uterine infections linked to common pathogens were playing a minor role as a cause for repeat breeder cows in this study. Alternative reasons for failure to conceive in these cows are discussed.